(untitled) (mathematica didactica, 2013)
This article presents first results of the research project ViStAD which is a qualitative video survey about the analog thinking of mathematical gifted children of the third and fourth grade. With the help of selected tasks in problem solving the focus is on the questions in which extent the abilities in recognizing analogies and the using of analogies attributes of mathematical gift are and how the approaches used by the children have an impact on the recognizing of analogies.